2023
DOI: 10.3389/fonc.2023.1120329
|View full text |Cite
|
Sign up to set email alerts
|

Syngeneic model of carcinogen-induced tumor mimics basal/squamous, stromal-rich, and neuroendocrine molecular and immunological features of muscle-invasive bladder cancer

Abstract: IntroductionBladder cancer is a heterogenous disease and the emerging knowledge on molecular classification of bladder tumors may impact treatment decisions based on molecular subtype. Pre-clinical models representing each subtype are needed to test novel therapies. Carcinogen-induced bladder cancer models represent heterogeneous, immune-competent, pre-clinical testing options with many features found in the human disease.MethodsInvasive bladder tumors were induced in C57BL/6 mice when continuously exposed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…We further confirmed the relevance of our FHBT models by projecting their RNA expression patterns onto principle component analysis plots of tumors from the TCGA-BLCA cohort (Fig. 2i ) and established N -butyl- N -(4-hydroxybutyl)-nitrosamine (BBN)-induced mouse bladder cancer models 15 (Extended Data Fig. 7b ) to show that they occupy overlapping space on the basis of histologic classification, indicating that the transcriptional features with the greatest variance between tumor subtypes are also conserved with FHBT models.…”
Section: Mainsupporting
confidence: 56%
“…We further confirmed the relevance of our FHBT models by projecting their RNA expression patterns onto principle component analysis plots of tumors from the TCGA-BLCA cohort (Fig. 2i ) and established N -butyl- N -(4-hydroxybutyl)-nitrosamine (BBN)-induced mouse bladder cancer models 15 (Extended Data Fig. 7b ) to show that they occupy overlapping space on the basis of histologic classification, indicating that the transcriptional features with the greatest variance between tumor subtypes are also conserved with FHBT models.…”
Section: Mainsupporting
confidence: 56%
“…Histopathologic and molecular characterization showed that the eight established tumour lines represented basal/squamous (BaSq), stromal-rich (SR) and neuroendocrine (NE)-like molecular subtypes. As reported for human tumours, cisplatin exhibited antineoplastic effects in a SR tumour line, while a BaSq line was found to be resistant [39 ▪ ]. To assess the effects of the histone deacetylase (HDAC) inhibitor chidamide on BC, Wang et al generated orthotopic models by instillation of N-methyl-N-nitrosourea (MNU) in the bladders of female Sprague–Dawley rats.…”
Section: In Vivo Modelsmentioning
confidence: 99%